From Reviews to Revenues Website Design’s Role in Converting Opinions into Purchase Intentions - Bernardus, Denny (Journal of Business & Applied Management, 2023)
This research is to examine and investigate the relationship between online reviews, web design, and buying interest in the context of online commerce. The purpose of this study is to investigate and investigate the relationship between online reviews and web design. According to the findings of this research, which employs both qualitative and quantitative methods, user reviews posted on the internet are an important tool for reducing informational inequality. This, in turn, influences consumer trust, which in turn influences the decisions that consumers make when they are making purchases. Concerns, however, including a lack of trustworthiness and the potential of incorrect evaluations, argue for a stronger level of intervention. These concerns call for an intervention level that is stronger. In this context, web design appears as a powerful moderating factor, having the ability to improve purchase confidence and interest by giving an appealing appearance and clear navigation. This can be accomplished through the use of a website that is well-designed. The findings of this study have management implications that can assist the e-commerce business in the creation of customer-focused platforms, ethical content efforts, as well as technological and design breakthroughs that break new ground. These findings also provide a framework for additional research, such as an investigation into the consequences of phony reviews, studies that cross cultural divides, and the development of tools to manage reviews. In general, the findings of the study offer substantial new insights into the ways in which online evaluations and website design interact to form the experience of shopping online. In addition to this, the study offers direction for the development of best practices in this highly competitive and ever-changing sector of the economy.